DUKUNGAN TIONGKOK TERHADAP PENGEMBANGAN NUKLIR DI IRAN PADA MASA PEMERINTAHAN HU JINTAO - Anggie Christiani (Universitas Komputer Indonesia, 2018)
This study aims to determine how the Chinese support towards nuclear development in Iran during the leadership of President Hu Jintao. Researchers conducting research ranging from how the relationship between China and Iran in general to the Chinese attitude forms specifically on nuclear development in Iran. Researchers using qualitative research methods with methods of descriptive analysis. Data obtained through the study of literature that researchers get while doing research into Indonesian Institute of Sciences and the embassy of China and Iran at Indonesia. The results of this study, explained that China pledged its full support for Iran's nuclear development for peaceful purpose and there is no indication to make weapons of mass destruction. In accordance with the policy of Hu Jintao in which Iran is a signatory to the non-proliferation treaty that has the right to develop peaceful nuclear aims, and if Iran violated the law on the nuclear issue, it must be done with diplomacy without having to give sanctions and pressure on Iran. The conclusion that can be drawn that China and Iran have a mutual dependency in order to meet the national interests of the country, so that the two countries support each other.